Digital Marketing Strategies of Tiktok Influencer "Mona Rahmawati" in Creating Culinary Appeal in East Cirebon - Moza Al Zahrani Firdaus; Farida Nurfalah (Greenation International Journal of Tourism and Management, 2026)
The development of digital technology has brought significant changes in marketing strategies, particularly in promoting culinary products through digital platforms. TikTok is used as a digital marketing medium because it is capable of reaching a wide audience and quickly generating consumer interest. This can be seen in the activities of TikTok influencer Mona Rahmawati, who utilizes TikTok as a digital marketing tool to promote culinary businesses in East Cirebon. This study aims to analyze the digital marketing strategies implemented by TikTok influencer Mona Rahmawati and to examine the responses of her followers and the community in East Cirebon based on the AIDA theory (Attention, Interest, Desire, Action). The research method employed is descriptive qualitative, using observation, interviews, and documentation as data collection techniques. The research informants include TikTok influencer Mona Rahmawati, her TikTok followers, the community of East Cirebon, and culinary MSME actors in the area. The results show that the digital marketing strategy carried out by Mona Rahmawati on TikTok involves creating culinary content with appealing visuals, clearly delivering information about price and taste, using distinctive hashtags, and actively interacting with the audience. These strategies are able to attract attention, generate interest and desire among the audience, and encourage them to make direct purchases. The findings indicate that Mona Rahmawati’s digital marketing strategy is effective in creating culinary appeal in East Cirebon.